Intense pulsed light: A promising therapy in treatment of acne vulgaris - Manjunatha Puttaiah; Shishira R. Jartarkar (Our Dermatology Online, 2017)
Background: Medical treatment of acne vulgaris includes a variety of topical and oral medications. Poor compliance, lack of durable remission, potential side effects are common drawbacks to these treatment. Therefore, there is a growing demand for a fast, safe and side effect free novel therapy. Light-based therapies are an attractive alternative acne therapy because they potentially offer more rapid onset and better patient compliance with a low incidence of adverse events. Aim: To study the efficacy of intense pulsed light in treatment of acne vulgaris. Materials and Methods: Twenty five patients with acne vulgaris were subjected to IPL. Baseline grading of acne was done. IPL was administered every 2weeks for 4 sessions. Grading was done after the end of treatment. Clinical photographs were taken for evaluation. Results: All patients showed a reduction in the number of acne lesions after 4 sessions of IPL. No significant side effects were noted. Patients also noted an improvement in skin texture. Conclusion: IPL showed beneficial effects in the treatment of acne.